Textbook in the context of modern educational technology - Natalia V. Pryadilnikova; Tatiana Y. Deptsova; Alexander A. Nechitailo (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The authors attempted to reveal the priorities of content, structure and creation of a conceptual model of the textbook of the new generation. Basing on the existing approaches the authors offer their vision of a textbook, presenting in a dialogue and interactive way the knowledge level of academic disciplines and interdisciplinary connections.